2015
DOI: 10.1542/peds.2014-3570
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Sensitivity in Parenting Preterm Children: A Meta-analysis

Abstract: BACKGROUND AND OBJECTIVES: Preterm birth is a significant stressor for parents and may adversely impact maternal parenting behavior. However, findings have been inconsistent. The objective of this meta-analysis was to determine whether mothers of preterm children behave differently (eg, less responsive or sensitive) in their interactions with their children after they are discharged from the hospital than mothers of term children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
97
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 122 publications
(112 citation statements)
references
References 85 publications
11
97
0
4
Order By: Relevance
“…Furthermore, we hypothesized that very preterm birth as a proximate of neurodevelopmental vulnerability would be related to regulatory problems. In contrast, we hypothesized that preterm birth would be unrelated to maternal sensitivity in accordance with findings of a recent meta-analysis [16]. …”
Section: Introductionsupporting
confidence: 53%
“…Furthermore, we hypothesized that very preterm birth as a proximate of neurodevelopmental vulnerability would be related to regulatory problems. In contrast, we hypothesized that preterm birth would be unrelated to maternal sensitivity in accordance with findings of a recent meta-analysis [16]. …”
Section: Introductionsupporting
confidence: 53%
“…This may be especially true for parents of VP infants born in the NICU whose self-efficacy may be diminished in this very stressful period with the infant medically at risk and partially cared for by others such as nurses. Although parents of VP/VLBW infants may not be overall less sensitive than those of term-born infants, 24 VP/VLBW infants may require a higher quality of parenting for favorable cognitive development.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 Furthermore, the finding that mothers of VP/VLBW show, on average, no differences in their sensitivity in interaction compared to FT mothers is also consistent with findings of a recent meta-analysis of thirty-four studies. 30 The investigation of the association between feeding problems and maternal sensitivity showed that in VP/VLBW infants, low maternal sensitivity was not a predisposing factor for feeding problems across infancy. Rather, when VP/VLBW infants had difficulties in feeding, there was a decline in subsequent maternal sensitivity at the next assessment point, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in line with the literature showing that the challenges of preterm birth do not translate into poorer maternal sensitivity. 30 There are some strengths and limitations of the study. The main strength of this study is that it assessed maternal sensitivity and feeding problems longitudinally at the same time points which allowed us to use a cross-lagged design.…”
Section: Discussionmentioning
confidence: 99%